Proposal of a novel integrated ocean thermal energy conversion system with flat plate solar collectors and thermoelectric generators: Energy, exergy and environmental analyses. (20th May 2020) - Khanmohammadi, Shoaib; Baseri, Mohammad Mehdi; Ahmadi, Pouria; Al-Rashed, Abdullah A.A.A.; Afrand, Masoud
Abstract: The present study deals with energy, exergy and environmental evaluation of an integrated ocean thermal energy conversion (OTEC) system include a flat plate solar collector, an organic Rankine cycle, an electrolyzer system boosted with a thermoelectric generator (TEG) unit. To precise assessment of suggested systems and determine the effects of adding thermoelectric generator to the system a comparative analysis is carried out. Two considered systems are solar ocean thermal energy conversion (S-OTEC) and solar ocean thermal energy conversion with thermoelectric (S-OTEC/TEG). A thermodynamic model is formed using Engineering Equation Solver (EES) to solve the set of linear equations governing on the component of the system. The result of exergy analyses shows that adding thermoelectric module to the S-OTEC results in exergy efficiency increment by 6.27%. Also adding thermoelectric unit to the system increase gross output power by 12.64 kW that the TEG pump input work in this case is 4.96 kW. Although the exergy destruction rate of the S-OTEC/TEG has a higher exergy destruction rate than S-OTEC, the exergy efficiency of S-OTEC/TEG is higher than S-OTEC. Environmental impact assessment criteria namely sustainability index (SI) and modified sustainability index (SI2), represent that applying TEG module to the system improves the SI2 while decreases the SI. Based on obtained results with methanol as working fluid, the SI change from 0.106 for S-OTEC to 0.183 for and S-OTEC/TEG system. In addition, the SI2 change from 1.949 to 2.220 when the TEG module added to the integrated system. Highlights: To propose a novel solar-based OTEC energy system. To compere the effect of adding a thermoelectric generator to the OTEC system To utilize the rejected heat to produce electricity using TEG To see the effect of design parameters on system performance